2003
DOI: 10.1007/s00704-003-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Measured and modelled contributions to UV exposures by the albedo of surfaces in an urban environment

Abstract: 1 SummaryThe increases in the erythemal UV exposures to horizontal planes and to inclined planes over three surfaces that are found in an urban environment (water, concrete and sand) due to the albedo of these surfaces have been estimated. For the cloud free case, the additional daily estimated UV exposures to a horizontal plane have a maximum value of 222 (J m -2 ) ER , where the index after the unit is there to indicate that it refers to a biologically effective exposure. In comparison, the daily erythemal U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…For water and most land surfaces the albedo is generally quite low (<5%) in the UV (e.g., Webb et al, 2004;Wendisch et al, 2004) and the UV ocean albedo is typically higher than the land albedo (Herman and Celarier, 1997). Sand surfaces can have higher albedo (Parisi et al, 2003). In general, spatial differences in land use (e.g., urban, agricultural, forest, etc.)…”
Section: Atmosphere-oceanmentioning
confidence: 99%
“…For water and most land surfaces the albedo is generally quite low (<5%) in the UV (e.g., Webb et al, 2004;Wendisch et al, 2004) and the UV ocean albedo is typically higher than the land albedo (Herman and Celarier, 1997). Sand surfaces can have higher albedo (Parisi et al, 2003). In general, spatial differences in land use (e.g., urban, agricultural, forest, etc.)…”
Section: Atmosphere-oceanmentioning
confidence: 99%
“…Irradiances on inclined surfaces affected by surrounding albedo have been previously explored [15][16][17]. Investigation of the biological effectiveness of the contribution to personal UV exposures due to the albedo of different horizontal and inclined surfaces has been investigated [18][19][20]. These effects are particularly important for outdoor workers' who should be aware of the contribution to UV exposures from such surfaces due to everyday working conditions [21].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the UV irradiance received on vertical surfaces has been carried out [11,19,23]. Webb et al [24] determined a relationship between vertical and horizontal irradiances.…”
Section: Introductionmentioning
confidence: 99%
“…This is 4 times larger than the commonly used albedo of 0.03 over grass. Parisi et al (2003) found that over some non-shaded parts of the city with high albedo (e.g. concrete surface) there is Fountoulakis et al (2016) discussed factors important for the UV spectral variability in Thessaloniki.…”
Section: Discussionmentioning
confidence: 99%